Redução do teor de sódio em biscoito salgado tipo aperitivo - Pieta, Fabiana (2016)
Excess sodium in foods has been identified as one of the increasing factors of chronic noncommunicable diseases (NCD's), among the most important is high blood pressure. Sodium is used in a wide range of foods, biscuits among them. However, some biscuits varieties have high sodium content, and for this reason the Ministry of Health established reduction levels for some categories of product. This study sought to reduce the sodium content in biscuit appetizer salted Mignon. For this, blends with limited surface were designed, that resulted in the development of 7 formulations with replacement of 30, 40, 45 and 60 %. Also, a control formulation with 100 % NaCl was created. This study aimed through the partial replacement of sodium chloride by other ingredients (Modified KCl - Nutek Salt® and PuraQ Arome NA4), to assess the impact of this substitution on the chemical parameters (moisture, aw, pH, sodium), physical (hardness) and sensorial (ADQ and affective test) of formulated biscuits. No significant differences (p> 0.05) for moisture, aw, pH and hardness of all F1-F7 and control formulations were found. To the sodium content results were statistically significant (p<0.05) between samples that had different percentage NaCl substituted, The reductions were gradual ranging from 943.43 to 637.21 mg/100g, and F7 with 60 % replacement reached the reference limit for biscuit Cream Cracker (699mg/100g). The formulation Control with 1214.04 mg / 100g of Na was compared to the sodium content of two commercial brands, both have lower content. The sensory profile was determined by quantitative descriptive analysis (QDA) using ten trained panelists and the results were submitted to analysis of variance (ANOVA), and Principal Component Analysis (PCA). Color uniformity, roast color, thickness, brightness, roast aroma, cookie arome Mignon, arome of bread, salty, sweet taste, aftertaste, hardness and crispness were the terms descriptors leading by trained judges. A significant difference was observed (p < 0.05) for salty taste, sweet taste and arome of bread. F4 formulation (40% replacement) was not significantly different from the control formulation for the salty taste. The first main component (PCA) showed variability between samples 84,65%, while the second shaft explained 11.54% of this variability. Affective tests were conducted with 100 consumers for the formulations Control, F4 and F7, the results showed that the substitution did not affect the acceptance of the product by the consumer in the evaluated attributes (flavor and overall impression), were not identified significant preference (p > 0.05) between formulations and both have more than 70 % of purchase intent. This work contributes to the biscuits segment industries seeking technical support for the reduction of sodium without this reduction affecting the sensory characteristics of the product.